Stability and mild of solutions forintegro-differential impulsive equations with infinite interval in a Banach space - Khelifa Daoudi, BerrezougHalimi, Mohamed Belaidi (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In this work, we establish several results about the stability, uniquenessand existence of mild solutions for integrodifferential impulsive equations with infiniteinterval in a Banach space; we assume that the linear part generates a strongly continuous semi group on a general Banach space. The arguments are based upon Banach and Leray-Schauder alternative fixed point theorems